Language Recognition on Translator of English and Indonesian Language (e-Journal of Linguistics, 2025)
This study investigated the preliminary step of language acquisition, which is language recognition, from translator of English and Indonesian language. It departed from the assumption that every bilingual speaker has/own the capability to do translation, albeit with different methods and through different processes subjectively. Through conducting experiment on translator, the level of language recognition of English and Indonesian translator along with any factors that can affect this level can be discovered. This study mainly aimed at discovering (1) the level of language recognition on translator of English and Indonesian language, as well as (2) other relevant factors that can affect the level of language recognition. The use of quantitative method through experimental linguistics was done to lecturers of English Department, Faculty of Humanities, Udayana University, using 10 trials of each language. The results showed was analyzed quantitatively based on the primary variables in language recognition of general translation on English and Indonesian. Generally, the level of language recognition is very dependent on visual recognition through phonological and conceptual representation. Moreover, several factors, such as age and sex, can also affect this language recognition level.